The purification and functional study of new compounds produced by Escherichia coli that influence the growth of sulfate reducing bacteria. Issue 1 (1st January 2020) - Oyewole, Oluwafemi Adebayo; Mitchell, Julian; Thresh, Sarah; Zinkevich, Vitaly
ABSTRACT: The induction and inhibition of sulfate-reducing bacterial (SRB) growth are of academic and biotechnological interests. The purification and functional study of two compounds produced by Escherichia coli were reported in this research. One of the compounds induces the growth of SRB and was termed as SRB growth enhancer (SGE) and the other inhibits their growth and was referred to as SRB growth inhibitor (SGI). The E. coli was cultured in M9 medium (1:20) and grown at 37°C for 24 h under limited oxygen condition. The cultures were spun and the supernatant was filter-sterilized. The cell-free supernatant was purified by ion-exchange chromatography and size exclusion chromatography. The fractions obtained were tested for inhibitory and enhancing activities of serially diluted Desulfovibrio indonesiensis, D. vulgaris and D. alaskensis . The effect of SGE and SGI on the morphology of SRB cells and biofilm formation was investigated using scanning electron microscopy (SEM) and atomic force microscopy (AFM). The structural analysis of purified SGE and SGI was carried out using matrix-assisted laser desorption ionization–time of flight (MALDI-TOF) spectrometry. SRB cultures in the presence of SGE showed two order of magnitude higher growths than untreated SRB cultures while with SGI they showed growth with two order of magnitude less. The SRB treated with the SGE improved the SRB growth while the inhibitor altered SRB morphology. The MALDI-TOF spectra in linear mode showed the compounds to be an oligomeric series with repeat 213 m/z unit between each peaks. The data revealed that the molecular mass of SGE is around 1700 Da while that of SGI is estimated as 2400 Da. The result of this study suggests that SGE can be used as a supplement in the media for rapid SRB detection while the SGI can be used for the prevention of SRB colonization.